Status Yuridis Aset Digital Produktif sebagai Objek Harta Bersama: Tinjauan Komparatif terhadap Praktik Digital Estate di Uni Eropa (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
This study aims to analyze the legal status of jointly managed social media accounts within the framework of marital property in Indonesia. The growth of the digital creative economy has transformed social media accounts into productive assets with economic value, yet Indonesian civil law has not provided legal certainty regarding their ownership status following divorce or death. The research method employed is normative legal research with a comparative legal approach. The results indicate a regulatory void in Law Number 1 of 1974, which remains oriented toward physical objects, while digital accounts are often regarded as personal rights tied to the registered individual. Conversely, digital regulations in the European Union, through the General Data Protection Regulation (GDPR) and the concept of digital estate, have begun to accommodate the continuity of access and management of digital assets for relevant parties. The discussion emphasizes the need for a redefinition of assets in Indonesian family law that synchronizes privacy rights with economic rights. In conclusion, productive social media accounts should be qualified as marital property through progressive interpretation or prenuptial agreements. This study recommends the synchronization of personal data protection regulations and marriage law to ensure distributive justice for couples in the digital economy era.